Early Life Modifiable Exposures and Their Association With Owner Reported Inflammatory Bowel Disease Symptoms in Adult Dogs - Hemida, Manal; Vuori, Kristiina A.; Moore, Robin; Anturaniemi, Johanna; Hielm-Björkman, Anna (Frontiers in Veterinary Science, 2021)
Background: Inflammatory bowel disease (IBD) is an idiopathic multifactorial disease in humans and dogs, usually assigned to the interactions between genes, gut microbiota, diet, environment, and the immune system. We aimed to investigate the modifiable early life exposures associated with IBD in dogs. Materials and methods: The study data was extracted from the validated owner-reported DogRisk food frequency questionnaire. This was a cross-sectional questionnaire-based study that tested 21 different early life dietary and environmental, demographic and genetic variables for their association with IBD or not, in adult dogs. A total of 7015 dogs participated in this study. The study covered early life periods; prenatal, neonatal, early and late postnatal periods. Two feeding patterns, a non-processed meat-based diet (NPMD) and an ultra-processed carbohydrate-based diet (UPCD) were studied. Data was analyzed using logistic regression analysis with a backward stepwise deletion. Results: From the final models we found that the NPMD during early and late postnatal periods were significantly associated with lower IBD risk later in life. The UPCD during the same periods was associated with a higher risk of IBD incidence. Also, the maternal diet during the neonatal period showed a non-significant trend of lower IBD risk in the offspring with the NPMD and a higher IBD risk with the UPCD. Additionally, the normal body weight of puppies during the first six months of age was associated with a lower risk of IBD in adulthood while, slim puppies associated significantly with IBD in adulthood. From the non-modifiable background variables, we identified the maternal history of IBD as the strongest risk factor for later incidence of IBD. Furthermore, male dogs were twice as likely to develop IBD as female dogs were. Conclusions: It is reassuring for owners to know that they themselves can have an impact on their dog’s health. A high-fat, low-carbohydrate NPMD exposure during early life and a normal body condition in puppyhood were significantly associated with less IBD in adult dogs. The opposite was true for UPCD exposure and abnormal body condition score in six month old puppies.